Vivência dos pais: à espera do transplante hepático para seu filho - Farias, Luryaga Porto (2009)
The need for a hepatic transplant for a child, whether due to a congenital problem or a contagious disease, results in a difficult situation in our times. This research aims at examining the emotional state of parents that are awaiting a hepatic transplant for their child. The research was carried out at the Liver Institute of Pernambuco (IFP) with the participation of four mothers. Semi-structured interviews were made using direct questions. A thematic analysis of the situation was made which permitted the identification of categories with qualitative representation and also of assessing nuclei favorable to the analysis of the situation. Results showed that the emotional state of the parents is markedly complex, expressed by the variety of categories and feeling the nuclei of which the situation is composed. The influence of diverse aspects relative to the participants which interfere in their emotional lives can be observed; these include: socioeconomic conditions, education and information levels, support network, different manners of dealing with the situation, age of the participants. It also includes the aspects of which the situation is composed: the therapeutics of the transplants and their details, losses, fears, risk of death, and possibility of failure. This study may contribute to the understanding of the situation, defining the difficulties, and addressing the attention needs of the parents, making way for the diverse component aspects of this complex phenomenon to be expressed